2021
DOI: 10.1002/cjce.24244
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anchoring performance of defective MgO nanotubes for lithium–sulphur batteries: A density functional theory (DFT) study

Abstract: In recent years, lithium–sulphur batteries have received great attention due to their high theoretical specific capacity. In the exploration of improving battery performance, developing suitable anchoring materials is one of the ways to suppress the shuttle effect which is one of the main problems of lithium–sulphur batteries. In this work, we investigated the anchoring ability of MgO nanotubes (MgONT) and defective MgO nanotubes (MgONTv) to lithium polysulphides (LiPSs) by density functional theory (DFT). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…The smaller the formation energy is, the easier the vacancy is to be generated. 41 The formation energy is difficult to obtain experimentally but can be calculated by DFT. The formation of carbon defects can be shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller the formation energy is, the easier the vacancy is to be generated. 41 The formation energy is difficult to obtain experimentally but can be calculated by DFT. The formation of carbon defects can be shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…25 greater than the adsorption energy of LiPSs on the materials listed in Table S1. 13,18,[44][45][46][47][48][49] Furthermore, it can be observed that the adsorption energies for short-chain Li 2 S n (n = 1, 2) on DSWNT are comparatively greater than those for long-chain Li 2 S n (n = 6, 8). This finding suggests that the former has a more favorable potential for inhibiting the shuttle effect.…”
Section: Resultsmentioning
confidence: 99%